Pendidikan dan Pelatihan Pemilahan Sampah Domestik untuk Meningkatkan Kesehatan Tubuh dan Rongga Mulut Warga RW 01 Kelurahan Grogol Petamburan - Dewi Liliany Margaretta; Rosalina Tjandrawinata; Dina Ratnasari; Harris Gadih Pratomo; Yessy Ariesanti (JURNAL ABDIMAS KESEHATAN TERPADU, 2023)
The problem of domestic waste in Indonesia related to the behavior of people who do not understand the impact of poor environmental hygiene which will lead to the emergence of various diseases in the body and oral cavity. Domestic waste is the remaining waste generated from household activities. Domestic waste is divided into organic that can be processed and inorganic that cannot be processed. The most pronounced impact is the emergence of various diseases such as intestinal worms, diarrhea, cholera, typhoid and anemia while infection can occur in the oral cavity so that infection can occur locally or systemically. Community Service (PkM) was carried out offline at the Grogol Petamburan Hall which was attended by 37 representatives of dasawisma and jumantik cadres, heads of RT 01 – 14 and RW 01. The material provided was in the form of various kinds of domestic waste (organic and inorganic), management of domestic waste, diseases that arise in the body and oral cavity due to a dirty environment, how to wash hands and how to brush your teeth properly in the form of ppt, e-flyer and video. Evaluation of success by conducting a pre and post test containing 10 knowledge questions and 10 attitude questions. There was an increase in participants knowledge of 22.3% and an improvement in attitude towards a better one. The results obtained from this activity are very good with partners willing to carry out PkM activities. At the end of the activity, toothpaste and a donation of trash bins were given to each RT.